-(r+s)-(2r+2s)=

Simple and best practice solution for -(r+s)-(2r+2s)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(r+s)-(2r+2s)= equation:


Simplifying
-1(r + s) + -1(2r + 2s) = 0
(r * -1 + s * -1) + -1(2r + 2s) = 0
(-1r + -1s) + -1(2r + 2s) = 0
-1r + -1s + (2r * -1 + 2s * -1) = 0
-1r + -1s + (-2r + -2s) = 0

Reorder the terms:
-1r + -2r + -1s + -2s = 0

Combine like terms: -1r + -2r = -3r
-3r + -1s + -2s = 0

Combine like terms: -1s + -2s = -3s
-3r + -3s = 0

Solving
-3r + -3s = 0

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '3s' to each side of the equation.
-3r + -3s + 3s = 0 + 3s

Combine like terms: -3s + 3s = 0
-3r + 0 = 0 + 3s
-3r = 0 + 3s
Remove the zero:
-3r = 3s

Divide each side by '-3'.
r = -1s

Simplifying
r = -1s

See similar equations:

| 4Z^5-8Z^3=0 | | -9y-4=31 | | 4(x+4)=x-4 | | n/2-10=88 | | 16z-48=42 | | 14z-48=42 | | -25+6x=29 | | b-8-2=11 | | -4r^2+10r+3=0 | | -4/5+7/9-3/10= | | 7(3)=4(3)+9 | | 3(4x^2-7)=5(x^2-3) | | (-p-8)-(2p-6)= | | f(x)=x^3-8x^2+30x-36 | | -6=n-14-5 | | x+(x-70)=248 | | -(x-4)=-44 | | (0.5)(-0.5)(3.2)(-7.9)(-2.4)(0)= | | -7r-3x+2=-8x+-8 | | (2y+12)=4y | | 19+6x=61 | | -7r-3x+2=-8x-8 | | 8(x+2)-3(x-4)=6(x+7)+8 | | 2(x^2-4)=2(3x^2+1) | | -11+3x=10 | | 8/9p-2/3^^^^^^^6_ | | 24+6x=78 | | 2g+8=23 | | n^2-4x+5=0 | | 4x^2-1=7x^2+9 | | (0.5)(-0.5)(3.2)(7.9)(-2.4)= | | -82-8x=22-12x |

Equations solver categories